2011
DOI: 10.1021/es200122r
|View full text |Cite
|
Sign up to set email alerts
|

Are Toxicological Responses in Laboratory (Inbred) Zebrafish Representative of Those in Outbred (Wild) Populations? − A Case Study with an Endocrine Disrupting Chemical

Abstract: Laboratory animals tend to be more inbred and less genetically diverse than wild populations, and thus may differ in their susceptibility to chemical stressors. We tested this hypothesis by comparing the responses of related inbred (theoretical inbreeding F(IT) = n + 0.25) and outbred (F(IT) = n) zebrafish (Danio rerio) WIK/Wild family lines to an endocrine disrupting chemical, clotrimazole. Exposure of inbred and outbred zebrafish to 2.9 μg clotrimazole/L had no effect on survival, growth, or gonadal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 51 publications
(77 reference statements)
2
37
0
Order By: Relevance
“…We found that elevating the temperature from 28°C to 33°C increased the somatic growth rate, but this growth increase was not the key determinant of sexual differentiation in our study (i.e., it did not favor the development of females). Instead, male-skewed sex ratios in the elevated temperature and/or clotrimazole exposure treatments appeared to be mediated by the inhibition of P450(CYP)19 aromatase, as has been found in other studies (39,40,42). Gene expression of cyp19a1a encoding aromatase was up-regulated in the few females remaining in the inbred, elevated temperature, and/or high-level clotrimazole exposure treatments, and we hypothesize that this up-regulation was the result of a compensatory response to P450(CYP)19 aromatase inhibition in these individuals.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We found that elevating the temperature from 28°C to 33°C increased the somatic growth rate, but this growth increase was not the key determinant of sexual differentiation in our study (i.e., it did not favor the development of females). Instead, male-skewed sex ratios in the elevated temperature and/or clotrimazole exposure treatments appeared to be mediated by the inhibition of P450(CYP)19 aromatase, as has been found in other studies (39,40,42). Gene expression of cyp19a1a encoding aromatase was up-regulated in the few females remaining in the inbred, elevated temperature, and/or high-level clotrimazole exposure treatments, and we hypothesize that this up-regulation was the result of a compensatory response to P450(CYP)19 aromatase inhibition in these individuals.…”
Section: Discussionsupporting
confidence: 57%
“…✗This "low dose × low temperature" treatment was not included in our analyses because we knew, from our previous work (40,83), that the lowdose clotrimazole (2 μg/L) alone would not affect population-relevant end points (survival, growth, gonadal development or fecundity), and we sought to maximize replication for the other treatment regimes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, laboratory Chironomus spp. cultures often suffer from genetic impoverishment (Nowak et al 2007b), reducing their similarity with the wild populations they are supposed to represent (Brown et al 2011). Genetic impoverishment also leads to inbreeding depression, which can compromise toxicological test results (Nowak et al 2007a).…”
mentioning
confidence: 99%